Optimizing Zakat Distribution: An Examination of Poverty, Income, and Unemployment in Kudus City - Rahmawati, Ira Ayuk; Qomar, Moh. Nurul (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
This study explores the optimization of zakat distribution in Kudus City, focusing on the effects of poverty, income, and unemployment. Employing a quantitative research method and the analysis of secondary data, this investigation employs EViews 10 for the examination of pertinent variables. Results from Kudus City indicate that the "Number of Poor Population," income, and unemployment significantly affect the "Zakat Almsgiving Funds." Notably, there is a negative correlation with the "Number of Poor Population" and a positive correlation with income and unemployment levels. These outcomes offer crucial insights for policy formulation and the enhancement of zakat distribution efficacy.